(3CSQGQ GdYQHjIs - (3YHO GdQMef Hf eMeO Hf YHjO Gddg GdCfUGQj , GHf GdCfHGQj, ceGd GdOjf CHh GdHQcGJ,J (B577 (3g` s
(3ChdgG (B:s
(3GdMeO ddg cGTa GdZWGA abO PcQJ aj gPG GdcJGH GdehShe HCSQGQ GdYQHjI cKjQkG ef ePGgH GdfMhjjf GdeJbOejf hGdeJCNQjf s
(3BNQgG (B:s
(3jQjO Ydi GdeGA, hgPG cdg djS HeWQO aj GdbjGS, hEfeG OYGge Edi Pdc cKQI GdGSJYeGd hgh GdTGP dG jbGS Ydjg aGYdeg hGddg Gdehab ddUhGH Je s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH GdChds
(3GfXQgG aj GdLRA GdChd (B9 (3fMhs
(3ChdgG hBNQgG Jedc HGSe Ydj Hf GdRHjQs
(3HgG fXGe GdJYbjHIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B3 - (3U (B327 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B5 - (3U (B183 ; (3gOjI GdYGQajf ddHZOGOi(B: (3L (B1 - (3U (B519s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B1 - (3bSe (B2 - (3U (B18 s
Keywords: (3GdfMhs